Incentives and constraints: An optimization mechanism for improving the performance of farmland protection entities - Zeyuan Li; Xiaoying Zhao (PLoS ONE, 2025)
Farmland is the most crucial resource for food production, and implementing farmland protection is a long-term strategy to achieve the sustainable use of this vital resource. Farmland protection is not only a priority for policymakers but also requires the cooperation of management departments and policy implementation bodies. Within China’s “county-township-village” farmland protection organizational structure, the current pressing issue is how to align the performance of grassroots governments using an incentive-constraint system and guide village-level cooperation to effectively implement farmland protection. This paper establishes a tripartite evolutionary game model focused on the incentive-constraint system for farmland protection, analyzing the demands and preferences of stakeholders and examining the strategic choices under the influence of multiple factors, such as farmland protection benefits, collusion behavior, accountability, financial support, and incentive-constraint standards. The optimal strategy combination for the tripartite game is discussed. The study found the following: (1) Village collectives tend to adopt active farmland protection strategies regardless of whether township governments provide financial support. (2) The increase in administrative rewards and punishments weakens the concealment behavior of township governments, becoming more effective as the success rate of assessments increases. (3) In areas with a high success rate of assessments, administrative incentives effectively improve stakeholder behavior; in areas with a low success rate, a higher level of incentive and constraint combinations can improve multi-party cooperation. (4) Administrative incentives for township governments must not fall below the administrative costs of strict supervision. Therefore, this paper proposes an optimization strategy for coordinating stakeholders in farmland protection in China. It suggests that county governments should strictly implement supervision and assessment, prioritize the use of incentive mechanisms to enhance the transparency of township government supervision, and encourage village collectives to develop a self-consciousness and behavior conducive to farmland protection.